Training Program and its Influence to Hotel Employee Performance - Putu Radharani Paramitha Sai Ishvari; I Gede Mudana; I Nyoman Rajin Aryana; Ni Made Sudarmini (International Journal of Glocal Tourism, 2020)
Purpose: This research aims to determine how much the influence of the training application based on need in increasing employee performance at a 5 star hotel in Nusa Dua tourist area, Kuta Selatan, Badung, Indonesia. Research methods: The technique of sample collection that used is simple random sampling with 50 employees of the hotel. The analysis technique used is simple linear regression. Findings: There was a positive influence from training to employee performance. The hypothesis test result shows training (X) had a positive influence to employee performance (Y). This is also shown through t-test value is (12,539) > t table (4,030) which is mean Ho rejected and Ha accepted. Implication: The training must be provided so that employees can work more efficiently and speed up time at work.